1994
DOI: 10.1021/ic00093a017
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Pseudoazurin from Achromobacter cycloclastes with Inorganic Redox Partners and Related NMR and Electrochemical Studies

Abstract: The effect of pH on rate constants (25 "C) for the [Co(dipic)2]-and [C0(phen)~]3+ oxidations of pseudoazurin pACu' have been studied in the pH range 3.5-8.7. From the trends observed (decrease in rate constants with decreasing pH) two pK. ' s are obtained, and from IH NMR these are confirmed as being associated with an active site His protonationfdeprotonation, pK, = 4.84 (average), and a protonationfdeprotonation of the uncoordinated H i d , pK, = 7.2 1 (average). Alongside plastocyanin and amicyanin, pseudoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
56
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 5 publications
8
56
1
Order By: Relevance
“…In blue copper proteins such as WT azurin, the C-terminal His is also at a similar location (47). Protonation of the C-terminal His ligand has been shown to occur in the reduced state of selected blue copper proteins such as plastocyanin, amicyanin, and pseudoazurin (48)(49)(50)(51)(52). However, no evidence for protonation has been found in the reduced state of other blue copper proteins such as azurin (53).…”
Section: Discussionmentioning
confidence: 99%
“…In blue copper proteins such as WT azurin, the C-terminal His is also at a similar location (47). Protonation of the C-terminal His ligand has been shown to occur in the reduced state of selected blue copper proteins such as plastocyanin, amicyanin, and pseudoazurin (48)(49)(50)(51)(52). However, no evidence for protonation has been found in the reduced state of other blue copper proteins such as azurin (53).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of a similar water molecule was found in A. faecalis pseudoazurin at both pH 7.8 and 7.0, while the peptide bond flip was found at only pH 7.0. Because the pK a values of the uncoordinated His 6 residue are 7.2 (reduce form) and 6.5 (oxidized form) (21), the protonation at His 6 may be the cause of the peptide bond flip in Al. faecalis pseudoazurin.…”
Section: Quality Of the Finalmentioning
confidence: 99%
“…Recent kinetic and theoretical studies on the blue copper protein plastocyanin have indicated the presence of two distinct electron-transfer sites: (i) the adjacent hydrophobic patch ϳ6 Å from the copper through which one of the histidine ligands protrudes, and (ii) the remote site involving and acidic patch region ϳ15 Å from the copper, with acidic residues on either side of the exposed 3 ] 3ϩ oxidation (21), indicating a clear preference of the protein for anionic species. Moreover, the self-exchange rate constant for reduced molecule (about 3 ϫ 10 3 M Ϫ1 s Ϫ1 ) is much smaller than those of most other cupredoxins and is quite similar to that found in higher plant plas-tocyanins (22).…”
mentioning
confidence: 99%
See 2 more Smart Citations